If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(x+6)-1=6x-8
We move all terms to the left:
9(x+6)-1-(6x-8)=0
We multiply parentheses
9x-(6x-8)+54-1=0
We get rid of parentheses
9x-6x+8+54-1=0
We add all the numbers together, and all the variables
3x+61=0
We move all terms containing x to the left, all other terms to the right
3x=-61
x=-61/3
x=-20+1/3
| 8x+4-4(-3x-1)=2(x-3) | | 9s+8s=-85 | | 8+7(n)=22 | | 3w-w-2w+10w=20 | | 19z+2z^2+24=0 | | 3/2y+y=9/2y | | -4(3y-3)+7y=5(y+2) | | 11z-3z-7z+1=12 | | -1=9+d | | 4(z+3)=- | | 5(x-4)+10-6=20-5-3+1-6 | | 15r-12r-r-r=14 | | -23y=-126 | | 3+3(5v-2)=-2(3v-6)+3v | | 10=(-8)+n/4 | | 18-4x=24 | | -3.2s=28.8 | | 14=11+a/3 | | -5=0.2k | | 18g-13g-4g+1=16 | | 6w-5=-5+8(w-1) | | 2=-2x-16 | | 3+3(5v-2)=2(3v-6)+3v | | (4x/2-15/2)+(x/10-3/10)=-3 | | 3v^2-81=0 | | 5x−12=2x+24∘ | | 1250+16t^2=H | | 7x+21=16x | | 6/7+x=2/3 | | 3x+16=-4+7x | | 2y+15=-45 | | 23+88-y=99 |